APPLYING CUSTOMARY INTERNATIONAL LAW IN THE INDONESIAN HUMAN RIGHTS COURT: AN ISLAMIC SOLUTION OF THE CONUNDRUM - Fajri Matahati Muhammadin; Muhammad Awfa; Kirana Anjani, (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2019)
Through Act No. 26 of 2000, Indonesia has established a Human Rights Court to put alleged perpetrators of genocide and crimes against humanity on trial. However, one problem seems to elude attention namely, customary international law is binding in international law. However, the Indonesian legal system particularly in the criminal justice system has no formal legal platform to justify the use of customary international law as legal basis. Be that as it may, the Human Rights Court has, in practice, applied customary international law on the basis of necessity to genocide and crimes against humanity. The aforementioned problem has thus been ignored. Using a doctrinal research method, this article finds that the crux of the problem is the strict formal legality principle applied in the Indonesian criminal justice system. This article argues that a solution can be found in the Islamic legal system which is not entirely foreign to Indonesia. Islamic criminal law recognizes the importance of certainty and legality but provides some room for limited flexibility parallel to what a material legality principle would dictate. It is argued that adopting the Islamic system would solve the main crux of the problem that is, the type of legality principle used.